Representing Arab-Indonesian identity: Language and cultural narratives on social media - Pujiati Pujiati; Adri Lundeto; Ikmal Trianto (Indonesian Journal of Applied Linguistics)
This study explores how Arab-Indonesian identity is represented and negotiated on social media platforms, focusing on Instagram and Facebook, through the lens of Critical Discourse Analysis. Arab-Indonesians, descendants of Hadhrami migrants, embody a hybrid identity that merges Arabic heritage with Indonesian cultural elements. The research examines how linguistic and cultural strategies, including Arabic loanwords, bilingual code-switching, religious hashtags, and visual symbols such as traditional attire, calligraphy, and cultural practices, are used to articulate identity in digital spaces. Findings highlight the strategic use of Arabic phrases such as Alhamdulillah (praise be to God) and InshaAllah (God willing) alongside Indonesian language, reflecting linguistic hybridity and cultural pride. Code-switching between Arabic and Indonesian in captions and comments serves as a dynamic tool for expressing dual cultural affiliations. Additionally, hashtags such as #ArabIndonesian and #TradisiArab amplify representation and foster community solidarity. Visual elements like jubah and abaya, Arabic calligraphy, and depictions of cultural celebrations reaffirm cultural heritage and assert identity in Indonesia’s multicultural society. Social media enables Arab-Indonesians to navigate cultural hybridity, balancing the preservation of Arabic traditions with integration into Indonesian contexts. These platforms also provide opportunities to challenge stereotypes, share positive narratives, and enhance cultural visibility. This study contributes to the understanding of hybrid identities, demonstrating how digital platforms facilitate the interplay between language, culture, and technology in identity construction. The research, however, has limitations. It focuses exThis study explores how Arab-Indonesian identity is represented and negotiated on social media platforms, focusing on Instagram and Facebook, through the lens of Critical Discourse Analysis. Arab-Indonesians, descendants of Hadhrami migrants, embody a hybrid identity that merges Arabic heritage with Indonesian cultural elements. The research examines how linguistic and cultural strategies, including Arabic loanwords, bilingual code-switching, religious hashtags, and visual symbols such as traditional attire, calligraphy, and cultural practices, are used to articulate identity in digital spaces. Findings highlight the strategic use of Arabic phrases such as Alhamdulillah (praise be to God) and InshaAllah (God willing) alongside Indonesian language, reflecting linguistic hybridity and cultural pride. Code-switching between Arabic and Indonesian in captions and comments serves as a dynamic tool for expressing dual cultural affiliations. Additionally, hashtags such as #ArabIndonesian and #TradisiArab amplify representation and foster community solidarity. Visual elements like jubah and abaya, Arabic calligraphy, and depictions of cultural celebrations reaffirm cultural heritage and assert identity in Indonesia’s multicultural society. Social media enables Arab-Indonesians to navigate cultural hybridity, balancing the preservation of Arabic traditions with integration into Indonesian contexts. These platforms also provide opportunities to challenge stereotypes, share positive narratives, and enhance cultural visibility. This study contributes to the understanding of hybrid identities, demonstrating how digital platforms facilitate the interplay between language, culture, and technology in identity construction. The research, however, has limitations. It focuses exclusively on Instagram and Facebook, excluding other platforms like YouTube or TikTok, and relies on publicly accessible content, potentially missing private community discussions. Future studies could explore audience responses and extend the scope to other digital and offline spaces, offering a more holistic understanding of Arab-Indonesian identity representation.clusively on Instagram and Facebook, excluding other platforms like YouTube or TikTok, and relies on publicly accessible content, potentially missing private community discussions. Future studies could explore audience responses and extend the scope to other digital and offline spaces, offering a more holistic understanding of Arab-Indonesian identity representation.